THE STUDY OF LINGUISTIC PROBLEMS IN LEARNING SPEAKING SKILL - Muhammad Syauqy Nu'man (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This study aims to describe the linguistic problem faced by students in MA NU 03 Sunan Katong Kaliwungu Kendal in learning speaking and the students’ ways to resolve it. The method in this study was qualitative descriptive. XI grade in MA NU 03 Sunan Katong Kaliwungu were the population in this study which is XI social 3 as the sample by doing lowest sampling from all the class in XI grade. The data used in this study were observation, questionnaire, interview, and documentation. The instrument of this research consist of the question of interview was adapted from Heriansyah (2012) and Robah (2021) and the questionnaire was adapted from Balqisa et al. (2020). The findings of this study showed that the student’s speaking performance was still low. The students have several linguistic problems in learning speaking based on students’ belive. Poor of grammar was dominated linguistic problem faced by students continued with a lack of vocabulary. Moreover, the third dominated linguistic problem in speaking was a lack of pronunciation. To overcome the linguistic problem, the students had several strategies to solve their problem in speaking such as using handphone to increase vocabulary and pronunciation, reading some book, listening to music, and watching films to improve vocabulary, asking to friend and teacher to get more information, and practice with their own self or with their friends in the class. Based on the findings, it gifts the information about the linguistic problem faced by students in English and their way to solve their problem in learning. In this case, the teacher was supposed to make new treatment for learning English in the future related in the students perspective keywords: Linguistic Problem, Learning Speaking